Issues of cancer survivorship : an interdisciplinary team approach to care - Kantor, Debra; Suzan, Zelda (Wolters Kluwer, 2016)
"Millions of patients with cancer are now surviving the five-year mark, and are dealing with the long-term negative impact of both illness and treatment therapies. This rare standardized resource is written by nurses highly experienced in oncology care, and emphasizes interdisciplinary teamwork. It also expertly guides nurses through the new requirements of oncology services: protocols for meeting the sensitive clinical and psychosocial aspects of cancer as a chronic illness."--